INTEGRATING ONE OF INTERNAL STRUCTURE OF DISCOURSE CALLED ‘PROCESS’ IN WRITING PROCEDURE TEXT FOR INTERMEDIATE LEVEL - Emilia Widuri (PRASASTI: Journal of Linguistics, 2019)
In this article the researcher applies one of internal structure of discourse called ‘Process’ in writing ‘Procedures text’. Procedure text is a piece of writing that tells us information of making/doing something through several steps/directions. There are two important parts that students have to consider in procedure text; the generic structure and the language features. In the language features, the internal structure of “Process” of discourse integrated. The aim of internal structure of “Process” are offers the procedure/process for how something is done/created. The problem occurs when students ignore the internal structure of discourse, therefore they will face difficulties in writing process.The first step of the researcher did in this research was making a lesson plan and student’ assessment. After finish it the researcher discussed with the expert to get the feedback. Based on the feedback the researcher revised it. Once again researcher discussed with the expert to get the final result of lesson plan and student’ assessment. The next step was conducting try out. It was held on 28th December 2017. The subjects are 3 students of UNY. The subjects are chosen randomly. Based on the research finding, internal structure is applicable in writing. The generic structure and language features are also really helpful for students in writing English especially procedures text. Thus, all of the subjects of the research be able to produce discourse part with the same structure and successfully produce a paragraph of procedure text.